Fatal Cobalt Toxicity after a Non-Metal-on-Metal Total Hip Arthroplasty. (27th August 2017) - Peters, Rinne M.; Willemse, Pax; Rijk, Paul C.; Hoogendoorn, Mels; Zijlstra, Wierd P.
Abstract : This case illustrates the potential for systemic cobalt toxicity in non-metal-on-metal bearings and its potentially devastating consequences. We present a 71-year-old male with grinding sensations in his right hip following ceramic-on-ceramic total hip arthroplasty (THA). After diagnosing a fractured ceramic liner, the hip prosthesis was revised into a metal-on-polyethylene bearing. At one year postoperatively, X-rays and MARS-MRI showed a fixed reversed hybrid THA, with periarticular densities, flattening of the femoral head component, and a pattern of periarticular metal wear debris and pseudotumor formation. Before revision could take place, the patient was admitted with the clinical picture of systemic cobalt toxicity, supported by excessively high serum cobalt and chromium levels, and ultimately died. At autopsy dilated cardiomyopathy as cause of death was hypothesized. A third body wear reaction between ceramic remnants and the metal femoral head very likely led to excessive metal wear, which contributed systemic cobalt toxicity leading to neurotoxicity and heart failure. This case emphasizes that fractured ceramic-on-ceramic bearings should be revised to ceramic-on-ceramic or ceramic-on-polyethylene bearings, but not to metal-on-polyethylene bearings. We aim to increase awareness among orthopedic surgeons for clinical clues for systemic cobalt intoxication, even when there is no metal-on-metal bearing surface.